z 5 zapisz wjak najprostszej postaci:
a) (x+3y)^2-9v^2=
b)4x^2+1-(2x+1)^2=
c)2(3+b)^2-12b=
d) (x-2)^2-(x+1)^2=
a) (x+3y)^2-9v^2= x² + 6xy + 9y² - 9v²
b)4x^2+1-(2x+1)^2= 4x² + 1 - 4x² - 4x - 1 = -4x
c)2(3+b)^2-12b= 2(9 + 6b + b²) - 12b = 18 + 12b + 2b² - 12b = 18 + 2b²
d) (x-2)^2-(x+1)^2= x² - 4x + 4 - x² - 2x - 1 = -6x + 3
a)
b)
c)
d)
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
a) (x+3y)^2-9v^2= x² + 6xy + 9y² - 9v²
b)4x^2+1-(2x+1)^2= 4x² + 1 - 4x² - 4x - 1 = -4x
c)2(3+b)^2-12b= 2(9 + 6b + b²) - 12b = 18 + 12b + 2b² - 12b = 18 + 2b²
d) (x-2)^2-(x+1)^2= x² - 4x + 4 - x² - 2x - 1 = -6x + 3
a)
b)
c)
d)